2002
DOI: 10.4049/jimmunol.169.5.2570
|View full text |Cite
|
Sign up to set email alerts
|

Subset-Specific Reductions in Lung Lymphocyte Accumulation Following Intratracheal Antigen Challenge in Endothelial Selectin-Deficient Mice

Abstract: We previously demonstrated induction and expression of CD62E and CD62P in the lungs of mice primed and then challenged with intratracheal (i.t.) SRBC. The current study examined accumulation of endogenous lymphocytes in the lungs of endothelial E- and P-selectin-deficient (E−P−) mice after i.t. SRBC challenge. Compared with syngeneic wild-type (wt) mice, E−P− mice showed an 85–95% decrease in CD8+ T cells and B cells in the lungs at both early and late time points. In contrast, CD4+ T cell accumulation was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 78 publications
2
14
0
Order By: Relevance
“…Thus, lung DC appear to migrate to lung tissue during inflammation in an endothelial selectin-independent fashion, in contrast to the case in the inflamed skin (15). Analysis of identically treated E Ϫ P Ϫ mice showed reductions in numbers of CD4 ϩ , CD8 ϩ , and CD19 ϩ cell in both lung mince and BAL that were very similar to those we have described previously (data not shown) (32).…”
Section: Accumulation Was Not Impaired In Mice Lacking Endothelialsupporting
confidence: 69%
See 3 more Smart Citations
“…Thus, lung DC appear to migrate to lung tissue during inflammation in an endothelial selectin-independent fashion, in contrast to the case in the inflamed skin (15). Analysis of identically treated E Ϫ P Ϫ mice showed reductions in numbers of CD4 ϩ , CD8 ϩ , and CD19 ϩ cell in both lung mince and BAL that were very similar to those we have described previously (data not shown) (32).…”
Section: Accumulation Was Not Impaired In Mice Lacking Endothelialsupporting
confidence: 69%
“…challenge (27) and have shown that endothelial selectins are required for recruitment to the lungs of some lymphocyte subsets (B cells and CD8 cells at all time points, and CD4 cells early after i.t. challenge) (30,32). However, because absence of endothelial selectins does not reduce recruitment of granulocytes or total mononuclear phagocytes, nor impair the ability to prime lymphocytes via the i.p.…”
Section: Accumulation Was Not Impaired In Mice Lacking Endothelialmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies, however, also report on impaired leukocyte extravasation into peripheral organs (39,45). In endothelial E-and P-selectin-deficient mice that have been intratracheally primed and challenged with SRBCs, a similar, only delayed CD4 ϩ T cell infiltration into the lungs was observed, suggesting that selectins do not seem to play an important role in T cell homing to the lungs (46). With respect to mycobacterial infections, at least P-selectin has been shown to be dispensable for leukocyte recruitment and granuloma formation (47).…”
Section: Discussionmentioning
confidence: 93%